Clinicopathological characteristics and prognosis of breast cancer patients with isolated central nervous system metastases in the multicentre ESME database. (February 2022) - Carausu, Marcela; Carton, Matthieu; Cabel, Luc; Patsouris, Anne; Levy, Christelle; Verret, Benjamin; Pasquier, David; Debled, Marc; Gonçalves, Anthony; Desmoulins, Isabelle; Lecouillard, Isabelle; Bachelot, Thomas; et al.
Background: As a result of progress in diagnosis and treatment, there is a growing prevalence of metastatic breast cancer (MBC) with isolated CNS metastases. This study describes the largest-to-date real-life cohort of this clinical setting and compares it to other clinical presentations. Methods: We retrospectively analysed the French Epidemiological Strategy and Medical Economics (ESME) MBC database including patients who initiated treatment for MBC between 2008 and 2016. Progression-free survival (PFS) and overall survival (OS) were estimated using the Kaplan–Meier method. Descriptive statistics and multivariate Cox model were used. Results: Of 22, 266 patients, 647 (2.9%) and 929 (4.2%) patients had isolated first-site CNS metastases or combined with extra-CNS metastases, with longer OS for the group with isolated CNS metastases (16.9 versus 13.9 months, adjusted HR = 1.69 (95% CI: 1.50–1.91), p < 0.001). Among the 541 (2.4%) patients with isolated CNS metastases and no intrathecal therapy (excluding leptomeningeal metastases), HER2+ cases were preponderant over TN or HR+ /HER2− cases (41.6% versus 26.1% versus 28.5%, respectively, p < 0.01). The treatment strategy consisted of a combination of local treatment and systemic therapy (49.2%), local treatment only (35.5%) or systemic therapy only (11.4%), or symptomatic therapy only (3.9%). Median PFS was 6.1 months (95% CI: 5.7–6.8). Median OS was 20.7 months (95% CI: 17.3–24.3), reaching 37.9 months (95% CI: 25.9–47.6) in the HR+ /HER2+ subgroup. Older age, TN subtype, MBC-free interval of 6–12 months, lower performance status, and WBRT were associated with poorer survival. Patients who received systemic therapy within 3 months from MBC diagnosis had longer OS (24.1 versus 16.1 months, p = 0.031), but this was not significant on multivariate analysis [HR = 1.0 (95% CI: 0.7–1.3), p = 0.806]. Conclusions: Patients with isolated CNS metastases at MBC diagnosis represent a distinct population for which the role of systemic therapy needs to be further investigated in prospective studies.